MOSQUITO LARVICIDAL AND ANTIMICROBIAL PROPERTIES OF ETHYL ACETATE CRUDE EXTRACTS OF CLADOSPORIUM SPHAEROSPERMUM AND CLADOSPORIUM MACROCARPUM - K PRANAY KUMAR; SHRUTI S DESHPANDE; SUNIL MISRA (International Journal of Pharma and Bio Sciences, 2016)
The main objective of this study is to investigate the ethyl acetate crude extracts of Cladosporium macrocarpum (MTCC 2137) and Cladosporium sphaerospermum (MTCC 2805) for their larvicidal activity against third and fourth instar larvae of A. aegypti and antimicrobial activity on few selected bacterial and fungal strains. C. macrocarpum extracts showed more susceptible to the third instar larvae than that of fourth instar larvae after 24hr of exposure (LC50 =116.36 ppm and 196.72 ppm; LC90 =577.84 ppm and 1604.98ppm) respectively. In the case of C. sphaerospermum extract also showed good larvicidal activity with (LC50 = 182.90 ppm and 248.96 ppm; LC90 = 1243.54 ppm and 1435.3ppm) against third and fourth instar mosquito larvae respectively. In the antimicrobial activity of the extract of C. sphaerospermum exhibited good antibacterial activity against S. aureus, P. aeroginosa, C. albicans and C. rugosa those are known to cause skin lesions and wound infections. From this study it is inferred that, mosquito larvicidal properties of both the extracts showed potent larvicidal activity against A.aegypti which can be exploited further for eco-friendly control of mosquito larvae as well as the effectiveness of the both crude extracts against possible usage in skin lesions and wound infections as therapeutic agents.